Modeling of ionospheric irregularities during geomagnetically disturbed conditions over African low-latitude region - Mungufeni, Patrick; Habarulema, John Bosco; Jurua, Edward (Space Weather, 2016)
In this study, station-specific models of ionospheric irregularities over low-latitude African region during geomagnetically disturbed days (Dst ≤ −50 nT) have been developed. Global Navigation Satellite Systems (GNSS)-derived ionospheric total electron content (TEC) data during 1998–2014 were used. Ionospheric irregularities were represented with the rate of change of TEC index (ROTI). The inputs for the models are the local time, solar flux index, day number of the year, auroral electro jet, and the disturbance storm time indices, while the output is the hourly median ROTI during these given conditions. To develop the models, the ROTI index values were binned based on the input parameters and cubic B splines were then fitted to the binned data. Developed models were validated with independent data over stations within 680 km radius. The models reproduced fairly well the inhibitions and the occurrences of ionospheric irregularities during geomagnetically disturbed days. The models even emulated these patterns in the various seasons, during medium and high solar activity conditions. During validations of the models, the percentages of the number of errors (difference between the observed and the modeled ROTI) <0.05 total electron content unit, 1TECU = 1016 el m−2 (TECU)/Min at all the stations were all >70% and the root-mean-square error were mostly < 0.1 TECU/Min. Furthermore, the correlation coefficients ranged from 0.47 to 0.76.
Keywords: Modeling of ionospheric; Irregularities; Geo-magnetically; Disturbed conditions; African low-latitude; Region